Kontribusi BKM Masjid Agung Bakrie dalam Membina Keberagamaan Masyarakat Kota Kisaran Kabupaten Asahan - Islamay, Putri Amanda; Daulay, Maraimbang; Ekowati, Endang (YASIN, 2023)
The background of this research is that a mosque is a house of worship for Muslims or Muslims. Mosque means a place of prostration, other names related to mosques in Indonesia are musholah, langgar or surau. The term is intended for buildings resembling mosques that are not used for Friday prayers, iktikaf, and are generally small in size. Besides being used as a place of worship, the mosque is also the center of the life of the Muslim community. Holiday celebrations, discussions, religious studies, lectures and Al-Qur'an study are often held in mosques. The purpose of this study was to find out how the contribution of the BKM Bakrie Grand Mosque in Kisaran City, Asahan Regency in fostering the diversity of the people of Kisaran City and how the response from the surrounding community was regarding the activities carried out by the BKM Bakrie Grand Mosque. This type of research uses field research, namely research that is directly carried out in the field or on respondents. This study uses a qualitative method with a Social Theology approach. The results of the study show that the management of the mosque is going well, judging from the planning that has been done. Organizing in BKM Masjid includes the areas of Imarah, Ri'ayah and so on. The Bakrie Great Mosque BKM also highly upholds the value of diversity, the Bakrie Great Mosque BKM instills the values of diversity in the community, to maintain that diversity the BKM maintains tolerance or maintains inter-religious harmony because to avoid inter-religious conflict caused by an attitude of feeling right in religion but still according to Muslims Islam is the true religion